ORGANIZATIONAL CHANGE AND EMPLOYEE STRESS: EMPIRICAL ANALYSIS OF EMPLOYEES IN THE REPUBLIC OF NORTH MACEDONIA - Andrijana Ristovska; Ljupco Eftimov (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
This paper addresses the issue of the importance and necessity of introducing constant organizational changes and their impact on employee stress as one of the primary pull factors of the employee turnover intention. In this regard, human resource managers in organizations are becoming increasingly aware that hiring and retaining talents are the most important determinants of success in the complex global world and that they must work more intensively on modernizing the process of change management to help employees, not only for acceptance, but also for their involvement in the change implementation process. The number of respondents from the processed data so far is 439 employees (differing according to their demographic characteristics). The purpose of this paper is to determine whether there is a statistically significant difference between the four different types of organizational change according to the Cummings and Worley (2014) organizational change classification (Human process changes; Techno-structural changes; Human resource management changes and Strategic changes), regarding their impact on the employee emotional state, as well as which type of organizational change has the most significant impact on employee stress in the Republic of North Macedonia. The survey findings contributed to the conclusion that Macedonian employees in terms of their feelings of fear, anxiety, nervousness, etc., equally perceive the impact of the different types of organizational change. More specifically, there are no statistically significant differences between the impacts of the different types of organizational change over the stress they face because of these changes.
Keywords: organizational change; human process changes; techno-structural changes; human resource management changes; strategic changes; stress; employee’ turnover intention.